Methicillin-Resistant Staphylococcus aureus Infection Is a Risk Factor for Unplanned Return to the Operating Room in the Surgical Treatment of a Septic Knee - Jaffe, David; Costales, Timothy; Greenwell, Patrick; Christian, Matthew; Henn, Ralph Frank, III (The Journal of Knee Surgery, 2017)
Surgical irrigation and debridement is the mainstay of treatment after the diagnosis of a septic knee. Arthroscopic treatment has been validated as a treatment option, but there is limited literature comparing it to an open arthrotomy regarding risk factors for failing single-stage surgical treatment. A retrospective review of surgically treated native adult septic knees at one urban tertiary care center was conducted to evaluate rates of unplanned return to the operating room (OR) following both arthroscopic and open treatment of an adult septic knee. The primary outcome studied was unplanned return to the OR for persistent infection within 4 months of the initial surgery. Demographics, laboratory, and microbiology data were collected to identify factors associated with unplanned return visits to the OR. Fisher's exact tests and two-tailed paired Student's t-tests were used for categorical and continuous data comparisons, respectively. A multivariate analysis was performed to identify independent risk factors of initial washout failure. Thirty-three patients underwent arthroscopy and 47 had open arthrotomy. Eight failed arthroscopy and nine failed open treatment (75.8 and 80.9% success rates, p = 0.59). Unplanned repeat washouts in arthroscopically treated knees was associated with methicillin-resistant Staphylococcus aureus (MRSA) (62.5 vs. 12%, p = 0.01) and increased synovial white blood cell (WBC) count (160,000 vs. 52,000, p = 0.004). Unplanned return for repeat washout after open treatment was associated with lower American Society of Anesthesiologists scores (2.3 vs. 2.9, p = 0.019). MRSA was the only independent predictor of failure of single washout in a multivariable logistic regression analysis (p = 0.017). This study did not detect a difference in success of single washout between arthroscopic and open treatment of septic arthritis. However, MRSA was identified as a risk factor for an unplanned return to the OR after arthroscopic treatment. Consideration should be made for open surgical treatment in the setting of MRSA infections of a native knee.
Keywords: MRSA; septic arthritis; knee arthroscopy; septic knee